IMPLEMENTASI PROGRAM PERLINDUNGAN DAN PENGAMANAN HUTAN PADA BALAI BESAR TAMAN NASIONAL LORE LINDU - Renaldi, Mohammad (Katalogis, 2015)
This study aims to identify and explain the policy implementation Forest Police Policy Implementation in the Great Hall of Lore Lindu National Park using qualitative research.Model of policy implementation approach using the theory of Van Metter and Van Horn by focusing on resource policy, communication and attitude number of informants in this study were five people.The results showed that the Forest Police Resources in BBTN Lore Lindu Office of Central Sulawesi Province there are still problems in the execution of its duties and functions and limited facilities and infrastructure owned by the Office of the BBTN Lore Lindu, of the phenomenon of communication the forestry police know, understand and knowwell on Forest Police Policy but still headwinds particular job description of each officer as well as the unavailability of financial support specifically allocated to support this policy so that still need improvement officer's level of understanding and skill, and attitude of the phenomenon, the game keeper very supportive Forest Police policy, although still required an increase in human resources.In an effort to increase police resources forestry, then need preparing master personal or employee duties; training, education on an ongoing basis; change the mindset of the forestry police officers to be more professional, has insight and feel responsible for the task in hand; debriefing training for forestry police should continue to be implemented; consider seriously if it will hold, transfer or promotion of forestry police officer.